Modes of control in international digital commerce: evidence from Amazon.com - Li, Jiatao; Chen, Ziyi; Kwon, Ohchan; Wang, Jue (Journal of International Business Studies, 2025)
Abstract Online marketplaces such as Amazon.com represent a new channel through which multinational enterprises (MNEs) can sell their products in foreign markets, either as third-party sellers or as suppliers to the platform owner. An MNE can have better control of the marketing mix when selling directly on Amazon.com as a third-party seller, but this task entails two challenges. First is the liability of foreignness, and second is the disadvantage of competing with other products that are directly sold by the platform owner. The platform owner sets the rules of the platform and has data and algorithmic advantages, putting competitive pressure on MNEs with tighter control. Data obtained from Amazon are analyzed and reveal that maintaining control as a third-party seller predicts lower sales than being a supplier to the platform owner. However, the penalty associated with retaining control is smaller for MNEs with more host-country experience and country-of-origin advantage. These findings provide new insights into how MNEs leverage platforms such as Amazon.com to expand their global reach.